2017
DOI: 10.12788/jhm2830
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in the AAP Bronchiolitis Quality Improvement Project

Abstract: BQIP participating sites maintained improvements in key bronchiolitis quality measures for 1 year following the project's completion. This approach, which provided an evidence-based best-practice toolkit while building the quality-improvement capacity of local interdisciplinary teams, may support performance gains that persist beyond the active phase of the collaborative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our results are consistent with those of previous studies that revealed that implementation of a bronchiolitis CPG successfully reduced the use of bronchodilators 3,[5][6][7][8]10 and CXR. [6][7][8][9][10] Decreased viral testing was achieved in the UCC and ED settings, consistent with the multisetting study by Tyler et al 10 Our results are also consistent with those of Bryan et al 11 who demonstrated adherence to a bronchiolitis clinical pathway was associated with shorter inpatient LOS and decreased ED costs. 11 These results support the use of a CPG as an effective tool to promote high-value care.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those of previous studies that revealed that implementation of a bronchiolitis CPG successfully reduced the use of bronchodilators 3,[5][6][7][8]10 and CXR. [6][7][8][9][10] Decreased viral testing was achieved in the UCC and ED settings, consistent with the multisetting study by Tyler et al 10 Our results are also consistent with those of Bryan et al 11 who demonstrated adherence to a bronchiolitis clinical pathway was associated with shorter inpatient LOS and decreased ED costs. 11 These results support the use of a CPG as an effective tool to promote high-value care.…”
Section: Resultssupporting
confidence: 92%
“…Despite these recommendations, significant variability in care and persistence of overtreatment exist nationally. [2][3][4] Since the updated AAP guideline, multisite quality improvement (QI) studies have been focused on improving individual components of the AAP bronchiolitis guideline in the inpatient [5][6][7][8] or emergency department (ED) settings 3,9 independently. There have also been successful collaboratives involving both inpatient and outpatient settings achieving decreased use of unnecessary tests and medications.…”
mentioning
confidence: 99%
“…Similar to Shadman et al and Sheft et al, we were able to demonstrate that protocol implementation resulted in improved adherence to clinical recommendations for children with bronchiolitis and resulted in shorter length of stay. 18,19 According to Scheft et al, strategies including the creation of specific discharge criteria within institutions as well as embedding the discharge criteria into daily notes can aid in improving adherence to protocols and recommendations. These strategies can empower physicians to discharge earlier when discharge is safe and appropriate.…”
Section: Discussionmentioning
confidence: 99%